Effects of functional remediation on neurocognitively impaired bipolar patients: enhancement of verbal memory. Issue 2 (21st September 2015) - Bonnin, C. M.; Reinares, M.; Martínez-Arán, A.; Balanzá-Martínez, V.; Sole, B.; Torrent, C.; Tabarés-Seisdedos, R.; García-Portilla, M. P.; Ibáñez, A.; Amann, B. L.; Arango, C.; Ayuso-Mateos, J. L.; et al.
Abstract : Background: Functional remediation is a novel intervention with demonstrated efficacy at improving functional outcome in euthymic bipolar patients. However, in a previous trial no significant changes in neurocognitive measures were detected. The objective of the present analysis was to test the efficacy of this therapy in the enhancement of neuropsychological functions in a subgroup of neurocognitively impaired bipolar patients. Method: A total of 188 out of 239 DSM-IV euthymic bipolar patients performing below two standard deviations from the mean of normative data in any neurocognitive test were included in this subanalysis. Repeated-measures analyses of variance were conducted to assess the impact of the treatment arms [functional remediation, psychoeducation, or treatment as usual (TAU)] on participants' neurocognitive and functional outcomes in the subgroup of neurocognitively impaired patients. Results: Patients receiving functional remediation ( n = 56) showed an improvement on delayed free recall when compared with the TAU ( n = 63) and psychoeducation ( n = 69) groups as shown by the group × time interaction at 6-month follow-up [ F 2, 158 = 3.37, degrees of freedom (df) = 2, p = 0.037]. However, Tukey post-hoc analyses revealed that functional remediation was only superior when compared with TAU ( p = 0.04), but not with psychoeducation ( p = 0.10). Finally, the patients in the functional remediation group also benefited from the treatment in terms of functional outcome ( F 2, 158 = 4.26, df = 2, p = 0.016). Conclusions: Functional remediation is effective at improving verbal memory and psychosocial functioning in a sample of neurocognitively impaired bipolar patients at 6-month follow-up. Neurocognitive enhancement may be one of the active ingredients of this novel intervention, and, specifically, verbal memory appears to be the most sensitive function that improves with functional remediation.